Digitalisasi Industri Perfilman Korea Selatan Melalui Netflix Sebagai Alternatif Pasar Ekspor Film - Faradina Tshania Laily; Adiasri Putri Purbantina (President University, 2021)
The global pandemic COVID-19 threatens both global health and the global economy, including the film industry. Throughout 2020, the international movie industry experienced a significant market decline due to various social distancing measurements. South Korea, enjoying its cultural export boom (e.g., Korean drama, Korean film), is not an exception. South Korean film industry experienced a sharp decline in their sales and revenue. The challenges from COVID-19 to the global film industry led to a market transformation, especially regarding global film distributions. Netflix, an online streaming platform, becomes one of the key players within this phenomenon. This paper employs a qualitative method to analyze the South Korean film industry's export strategy transformation through Netflix.[AE1] The paper found that South Korean film industries experienced a 13,3 % increase in exports in 2020, with 975 movies. There is increasing consumer interest in South Korean culture, actors, and stories as more Korean movies are accessible through Netflix.